The Correlation Between Knowledge Level and Maternal Anxiety in Neonatal Asphyxia at Banyumas Regional Public Hospital - Muhammad Nur Malik Ibrahim; Umi Solikhah (UM Purwokerto Press, 2024)
Background: Neonatal asphyxia refers to condition newborn baby experiences lack of oxygen, leading to brain damage or even death. There are several factors that make asphyxia babies experience respiratory failure, labor factors which include prolonged labor, actions such as vacuum extraction, forceps extraction and sectiocaesarea. that can be also be caused by birth depression, infections and drugs used during labour. Based on the background above, the problem formulation in this research is :What is the relationship between the level of knowledge of mothers of babies born with Asphyxia Neonatorum? How do mothers worry about babies born with Asphyxia Neonatorum?It is hoped that it can educate pregnant women about the health of their unborn babies and carry out various positive activities to provide health services and health education to pregnant women about baby asphyxia, especially community health centers which play an active role in examining pregnant women. Method: This study quantitative research design with a questionnaire. The research design used analytical survey using cross-sectional. Data analysis univariate and bivariate analysis using the spearman correlation. The sample 30 mothers of infants with asphyxia at Banyumas Regional Hospital, selected through simple random sampling from june-july 2023. The research include knowledge level (Guttman Scale) and anxiety (Likkert Scale). The Cronbach’s reliability (0,6). The reliability knowledge level 0.829, indicating good reliability. Results:The correlation analysis of 0.575, with significant p-value of 0.001, indicating sginificant correlation between knowledge level and maternal anxiety in neonatal asphyxia. Conclusion:There is significant correlation between knowledge level and maternal anxiety in neonatal asphyxia.